Enhancing medical students' communication skills: development and evaluation of an undergraduate training program - Hausberg Maria C (BMC Medical Education, 2012)
Abstract Background There is a relative lack of current research on the effects of specific communication training offered at the beginning of the medical degree program. The newly developed communication training "Basics and Practice in Communication Skills" was pilot tested in 2008 and expanded in the following year at the University Medical Centre Hamburg-Eppendorf in Germany. The goal was to promote and improve the communicative skills of participants and show the usefulness of an early offered intervention on patient-physician communication within the medical curriculum. Methods The students participating in the project and a comparison group of students from the standard degree program were surveyed at the beginning and end of the courses. The survey consisted of a self-assessment of their skills as well as a standardised expert rating and an evaluation of the modules by means of a questionnaire. Results Students who attended the communication skills course exhibited a considerable increase of communication skills in this newly developed training. It was also observed that students in the intervention group had a greater degree of self-assessed competence following training than the medical students in the comparison group. This finding is also reflected in the results from a standardised objective measure. Conclusions The empirical results of the study showed that the training enabled students to acquire specialised competence in communication through the course of a newly developed training program. These findings will be used to establish new communication training at the University Medical Centre Hamburg-Eppendorf.